Exploring the possible two-proton radioactivity of 38,39Ti - B. Huang; F.P. Bai; J.G. Li; D.Q. Fang; S.M. Wang (Physics Letters B)
Two-proton (2p) radioactivity represents a rare decay mode that has been experimentally observed only in a selected few nuclei. The exploration of 2p emission is crucial for elucidating the structure, mass, and nucleon-nucleon interactions within exotic proton-rich nuclei. 39Ti has long been postulated as a potential candidate for 2p emission; however, experimental investigations have yet to confirm its 2p decay. To provide more accurate information for further studies, we utilize the Gamow shell model (GSM) and the Gamow coupled channel (GCC) method to analyze the prospective 2p radioactivity of isotopes 38,39Ti. Our calculations suggest that 39Ti is indeed a viable candidate for 2p emission. Notably, the estimated partial 2p decay width for 39Ti, predicted from the three-body GCC method, suggests that its 2p decay could rival its β decay in likelihood, although this is highly dependent on the specific 2p decay energy. Additionally, our analysis indicates a propensity for pairing between the valence protons in 39Ti. A similar investigative approach reveals that 38Ti exhibits a higher 2p decay energy and a broader decay width than 39Ti, positioning it as a more promising candidate for 2p decay.